Encyclopedia of Life Sciences 2016
DOI: 10.1002/9780470015902.a0021231.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Stable Isotopes as Tools in Ecological Research

Abstract: Stable isotope analysis has proved to be an extremely useful tool in elucidating many ecological problems, with stable isotope ecology comprising the theme of a series of international conferences ( http://www.isoecol.org ). Stable isotopes can be used as biological tracers in the following ways: (1) to identify sources, for instance in determining the identity of basal carbon in a food web; (2) to distinguish sources, for example to determine whether a breeding animal is using loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 60 publications
0
14
0
Order By: Relevance
“…Despite their typically lower resolution than that of extrinsic methods, stable isotopes comprise a convenient tool with which to investigate migration. 7,8 In addition, since there is no attachment of bulky equipment the technique is ideal for small taxa. Furthermore, stable isotopes can distinguish migrants from residents within the same species; important since many insect species are partial migrants.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite their typically lower resolution than that of extrinsic methods, stable isotopes comprise a convenient tool with which to investigate migration. 7,8 In addition, since there is no attachment of bulky equipment the technique is ideal for small taxa. Furthermore, stable isotopes can distinguish migrants from residents within the same species; important since many insect species are partial migrants.…”
Section: Introductionmentioning
confidence: 99%
“…Intrinsic markers such as stable isotope analysis require only one capture to reveal potential information about origin and are therefore less costly. Despite their typically lower resolution than that of extrinsic methods, stable isotopes comprise a convenient tool with which to investigate migration 7,8 . In addition, since there is no attachment of bulky equipment the technique is ideal for small taxa.…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of the natural stable isotope compositions of organisms has been widely used to identify cryptic trophic interactions in food webs (Newton, 2016). Recent studies revealed its potential to unravel complex interactions between a free-living parasite and its hosts (Stapp & Salkeld, 2009;Schmidt et al, 2011;Demopoulos & Sikkel, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Stable isotopes can provide insights in this respect (Robinson, 2001;Rubenstein and Hobson, 2004;Perkins et al, 2014;Newton, 2016). The concept of the isotopic niche is based on the fact that an animal's chemical composition is influenced by what it consumes (Fry, 2006).…”
Section: Introductionmentioning
confidence: 99%